Principle of Equal Rights and Self-Determination of Peoples in the Context of Legal Nature of the Republic - Constituent Entity of the Russian Federation (on the example of the Republic of Kalmykia) - Evgeniy Gunaev (Oriental Studies, 2018)
The article is devoted to the questions of realization of the principle of equal rights and self-determination of peoples in the Russian Federation at the regional level.